Involvement of miR-205-5p in mediating the development of nodular thyroid disease associated with coal worker’s pneumoconiosis via pulmonary extracellular vesicles - Zhao, Feng; Hao, Yu; Zhang, Hongzhen (Frontiers in Endocrinology, 2025)
ObjectiveCoal worker’s pneumoconiosis (CWP) is an occupational disease, and the mechanisms underlying the development of its complication, nodular thyroid disease (NTD), remain unclear. This study aimed to investigate the role of miR-205-5p (miR-205-5p) in the development of nodular thyroid disease associated with coal worker’s pneumoconiosis.MethodsThe potential role of pulmonary extracellular vesicles in triggering coal worker’s pneumoconiosis-associated nodular thyroid disease was explored. RNA was extracted from isolated extracellular vesicle samples, and real-time fluorescent quantitative RT-qPCR was performed using specific primers and probes. The levels of miR-205-5p in the extracellular vesicles from the supernatant of each treatment group were compared, and the significant expression of miR-205-5p in the extracellular vesicles was detected by RT-qPCR to evaluate the regulatory role of lung-derived extracellular vesicles in the development of coal worker’s pneumoconiosis-associated nodular thyroid disease. In addition, cell proliferation, apoptosis, and invasion capabilities were assessed using the CCK-8 assay for cell proliferation activity, Annexin V-FITC/PI double staining and flow cytometry for cell apoptosis rate, and Transwell assay for cell invasion ability.ResultsBy isolating, purifying, and analyzing extracellular vesicles from coal worker’s pneumoconiosis patients and healthy controls, it was found that the expression of miR-205-5p in the plasma of coal worker’s pneumoconiosis patients was significantly higher than that in the healthy controls (P<0.01). Furthermore, the expression levels of ATF4 and CHOP were also significantly increased in coal worker’s pneumoconiosis patients (P<0.01), consistent with the expression trend of miR-205-5p. Further in vitro cell experiments demonstrated that miR-205-5p can promote the proliferation and formation of nodules in thyroid cells by regulating the expression of downstream target genes. This study revealed the critical role of miR-205-5p in the development of nodular thyroid disease associated with coal worker’s pneumoconiosis and provided new experimental evidence for the diagnosis and treatment of this disease.ConclusionmiR-205-5p in pulmonary extracellular vesicles mediates the development of nodular thyroid disease associated with coal worker’s pneumoconiosis through the ATF4/CHOP signaling axis. Further research is essential to comprehensively investigate the specific targets through which miR-205-5p derived from pulmonary extracellular vesicles triggers the development of nodular thyroid disease associated with coal worker’s pneumoconiosis via the ATF4/CHOP signaling axis.